Kinship and marriage - Fox, Robin (Middlesex, 1967)
Although the subject of kinship and marriage has long dominated anthropological thinking and teaching, there is no introductory book on it. Radcliffe-Brown's excellent introduction to African Systems of Kinship and Marriage (1930) is still the only piece of general work that can be recommended to first-year students and interested laymen, and it is rapidly becoming out of date. There are sections or chapters in some anthropological text-books of course, but these are rather brief. There is a need for a general book that will try to give an outline of some of the methods of analysis used in the anthropological treatment of kinship and marriage; a book that will be useful to the student approaching the subject for the first time, and of interest to the layman who wishes to know more about this central topic of social anthropology.
Keywords: Kinship